MOTIVATION OF INDEPENDENT LEARNING ACTIVITY OF STUDENTS OF HIGHER TECHNICAL EDUCATIONAL INSTITUTIONS - M.Yu. Martynenko; K.V. Pashyvkina (Academy of Cognitive and Natural Sciences, 2008)
The main aspects and points of professional motivation of the technical university students' self-work are determined in this article. The lecturer's functions within students' self-work, are de fined.